Revolving Rating Analysts and Ratings of Mortgage-Backed and Asset-Backed Securities: Evidence from LinkedIn - Jiang, John (X.); Wang, Isabel Y.; Wang, K. Philip (Management Science, 2018)
This study examines whether revolving rating analysts who transition from major rating agencies to issuers are associated with any rating inflation in the issuers’ mortgage-backed securities (MBS) or asset-backed securities (ABS). Using professional profiles posted on LinkedIn to identify revolving rating analysts with structured finance rating experience, we find that the more the issuers employ such analysts, the more likely that ratings of issuers’ MBS and ABS new issuances are inflated compared with otherwise similarly rated securities. Additional analyses show that the impact of revolving rating analysts is more pronounced in complex deals and when the revolving analysts are more senior, indicating that rating expertise in structured finance may play a role in MBS and ABS rating inflation. Finally, we find that at least for AAA-rated MBS and ABS, investors fail to see through the rating inflation associated with revolving rating analysts. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2921 . This paper was accepted by Shivaram Rajgopal, accounting.